PENOLAKAN DISPENSASI KAWIN ANAK DI BAWAH UMUR (Studi Penetapan Pengadilan Agama Manna Nomor 0024/Pdt.P/2018/PA.Mna) - Zulvayana, Zulvayana (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2018)
This study  aims to determine the legal considerations in rejecting the application of marriage  dispensation in the Manna  Religion Court and  to find out the determination of the Manna  Religion Court Number  0024  / Pdt.P  / 2018  / PA.Mna in accordance with the  elements  of legal justice, legal certainty  and  legal benefits.  Based  on the  results of the  research, it is known that the legal consideration of the refusal of marriage  dispensation applications because the Petitioners  in the trial only submitted 1 (one)  witness so that the applicants  could not prove  the argument of their petition  and  in court found  a fact that the children of the applicant  had been  married  before the application for marriage  dispensation was tried . The cause  of rejec- tion of marital dispensation of minors due to actions that are contrary  to Article 7 of Act Number  1 of 1974.  Determination of the Manna  Religion Court  Number  0024  / Pdt.P  / 2018  / PA.Mna is in accordance with the elements  of justice, certainty  and legal benefit because in the Determination of the application for marriage  dispensation is guided  by Law Number  1 of 1974. The results of this study, are expected to be a deterrent effect for the community and the Office of Religious Affairs, so as not to violate Law Number  1 Year 1974  by marrying minors without the Religion Court dispensation. The rejection of the granting of marriage  dispensation in substantial  justice will be difficult to be felt by the applicants, but in order to enforce procedural justice, the stipulation  of marital dispensation creates order in recording  marriage